Modeling the Impact of Community Awareness on the Dynamics of Cardiovascular Diseases - Gupta, Sagar (Butwal Campus Journal, 2023)
Cardiovascular disease (CVD) is caused due to high blood pressure, diabetes, poor diet and lack of exercises. Awareness about cause and preventive measures of the disease play a key role to control the prevalence of CVD in the communities. In this article a non-linear mathematical model is proposed and analyzed in which the number of CVD people in the communities is controlled by the awareness disseminated through the word of mouth. Aware people change their lifestyle that includes daily physical exercises, taking healthy food timely and live stress-free life etc. thereby preventing the onset of CVD and its complications. The awareness generation number R0 is calculated and it is found that the system undergoes transcritical bifurcation. Equilibria analysis and stability analysis are performed. Numerical analyses are performed to validate the analytical ﬁndings. The analysis of the model and the outcomes reveal that the density of the CVD people can be signiﬁcantly reduced by community awareness through word of mouth.